A Student Retention Strategy for Educational Leaders in International Programs at Thai Private Universities - Asavisanu1, Poonpilas; Mhunpiew, Nathara (Scholar: Human Sciences, 2014)
Factors affecting student retention were examined in the context of international programs at Thai private higher education institutions for the development of a leadership strategy to affect retention. A mixed-methods study involving both quantitative and qualitative aspects was employed to determine factors affecting student retention and current practices utilized.Students, faculty and administrators of international programs were surveyed and interviewed to obtain data for this study. Results indicated that retention of students in international programs at Thai private universities were influenced by academic, social, advising, and financial issues as well as levels of degree commitment, scholastic conscientiousness and academic efficacy. Current practices utilized included academic remediation, tutoring, advising, and student monitoring systems.These findings suggest that implementation of practical interventions supported by retention research and leadership commitment to increasing academic improvement will benefit students and have an impact on student retention.